2020
DOI: 10.1186/s12888-020-02814-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of humor expression on suicidal ideation among adolescents: mediating effects of depressive emotion and positive emotion

Abstract: Background The occurrence and degree of suicidal ideation during the past month in adolescents should be regarded seriously. Several studies have noted that humor expression style and depressive emotion may influence adolescents’ suicidal ideation. However, there is insufficient evidence concerning whether positive emotion reduces such suicidal ideation in adolescents. In addition, the relationships among humor expression, depressive emotion, positive emotion and suicidal ideation remain to be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Some studies have suggested that the use of humor can be a healthy tool for coping with life stress (Abel, 2002). In keeping with these competing issues, humor has been found to be both negatively and positively associated with suicidal ideation depending on the effect that it elicits (Lee et al, 2020). Further research is needed on the impact of humor and flippant messaging both on suicidality in general and on social media in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that the use of humor can be a healthy tool for coping with life stress (Abel, 2002). In keeping with these competing issues, humor has been found to be both negatively and positively associated with suicidal ideation depending on the effect that it elicits (Lee et al, 2020). Further research is needed on the impact of humor and flippant messaging both on suicidality in general and on social media in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, results of the supplementary subgroup analysis suggest that risk preference does not play a regulatory role in the first three text characteristics, thereby verifying that teenager students may express strong preference for numbers, symbols, and positive emotional characteristics. This finding may be ascribed to the adolescents’ constant use of symbols and numbers ( Ji et al, 2017 ), and positive emotions usually have a positive impact on adolescents ( Lee et al, 2020 ). By contrast, among the characteristics of emotional conflict not found preference at present, results of the subgroup analysis show that students who prefer having no emotional conflict in the text showed the characteristics of risk avoidance, or lower grades, or rural or school accommodation ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the type of humor style expressed could determine the kind of effect experienced. Lee et al tested the mediating roles of depressive symptoms in adolescents' humor expression and suicidal ideations [ 20 ]. The cross-sectional study found that adolescents who consistently used negative humor like 'self-deprecation' (modesty about or criticism of oneself) experienced more depressive emotions and suicidal ideations [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…Lee et al tested the mediating roles of depressive symptoms in adolescents' humor expression and suicidal ideations [ 20 ]. The cross-sectional study found that adolescents who consistently used negative humor like 'self-deprecation' (modesty about or criticism of oneself) experienced more depressive emotions and suicidal ideations [ 20 ]. At the same time, other types of negative humor like 'other-devaluing' (emphasizing other people's flaws or negative qualities) resulted in less suicidal ideation [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation